Pelatihan Budidaya Sayuran Hidroponik Dengan System Wick Di Kelurahan Sungai Pagar - Ika Wahyuningsihi; Putri Ahya Radhiya; Aminah Kurniati; Anugrah Rillo Pangestu; Endang Sulastri Dewi Atmojo; Febriani Febriani; Fauzan Ramadhan; Nadila Nadila; Ruzana Fitri; Bayhakki Bayhakki (Pusat Riset dan Inovasi Nasional, 2023)
This service aims to introduce a hydroponic vegetable cultivation system using the wick method in Sungai Pagar Village. The environment in Sungai Pagar Village is characterized by sandy soil due to the accumulation of peat soil, so plant cultivation activities are still limited. In this context the wick method is adopted as a relevant solution. Training activities were carried out through several stages, including field surveys, delivery of materials, sowing seeds, making AB mix nutrition, making a hydroponic wick system from used plastic bottles, and monitoring and evaluation. The results of the training showed an increase in participants' knowledge about hydroponic cultivation and their abilities in caring for hydroponic plants. Each training participant succeeded in making a hydroponic wick system using used plastic bottles and was given a hydroponic cultivation package to continue cultivation at home. In order to improve food security and the community's economy, this training made a positive contribution by introducing an environmentally friendly and hydroponic vegetable cultivation system. efficient. In conclusion, this training was successful in introducing and training the public in hydroponic vegetable cultivation using the wick method.